Farming System of Small and Marginal Farmers in Rainfed Areas - M., Kumaran,; kumar, J. Vasantha (Indian Journal of Extension Education, 2010)
Rainfed areas account for 68 per cent of India's net cultivated land and support about 360 million people which may rise to 600 million by 2020. Even after the realization of India's full irrigation potential by 2013, it is estimated that around 50 per cent of India's net cultivable area of 142 million ha will remain rainfed. Farming under rainfed conditions is risky because of its dependence on uncertain monsoon or rainfall and other limited inputs. More over majority of our rainfed holdings are small and marginal. Further, it is very difficult for the farm families to get adequate food and income from agriculture alone for their sustenance. A whole farm approach or an integrated farming system approach would be of great relevance to the small and marginal farmers to deal with such situations. Farming system is a complex inter-related matrix of soils, plants, animals, implements, labour and capital, inter-dependent farming enterprises which are unique and reasonably stable arrangement complementary to each other. Further, the farm family manages these enterprises in response to their physical, biological and socio economic environment, household goals, preferences and resources. Farming system concept as such is not new to our farmers who have been practicing mixture of plant and animal units in farming from time immemorial by combining crops with mulch animals and/or goats, sheep etc.